'Transmitting the message of Okinawa by drums': Representations of Japanese-ness and Okinawan-ness in Okinawan dance in Santa Cruz, Bolivia. Issue 2 (3rd July 2017) - Siemann, Yvonne
ABSTRACT: This paper examines the role of dance in identity construction among young descendants of Okinawan migrants who settled in Colonia Okinawa in Santa Cruz, Bolivia in the 1950s and 1960s. Ryūkyūkoku Matsuridaiko, a modernized form of eisā dance that is traditionally performed at the Buddhist soul festival Obon, offers a new way for these young descendants to reconnect to their ancestors' culture. For most observers and some practitioners, the colourful dance represents Japanese culture and values that in a Bolivian context are commonly related to the socio-economic success of this immigrant minority. However, my analysis of Ryūkyūkoku Matsuridaiko will demonstrate that the dance furthermore serves the need to negotiate issues of identity among the younger generation of an ethnic minority of Okinawan ancestry within the Japanese descendant minority. Drawing on participant observation and interviews from several stays in Santa Cruz between 2013 and 2016, my analysis illustrates how this dance is used to express and negotiate identity issues between Bolivia, Okinawa and Japan and how it connects to larger discourses of a multilocal Okinawan community.